Peran Branding Image dalam Mempertahankan Loyalitas Pelanggan : Studi Kasus pada Produk Yakult - Nurhanifah Nurhanifah; Abdi Verdiansyaf; Cindy Satika Lesmana; Elvira Zahra; Muhammad Raditia Handika; Syahraini Puspa Daulay (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2024)
This research was conducted to find out the role of branding image played by Yakult products to maintain customer loyalty. The method used in this research is descriptive qualitative. The data collection technique in this research is by conducting interviews with people who consume Yakult products. The data analysis technique in this research uses data presentation techniques and drawing conclusions to determine the results of this research. The results of this research are that branding image plays an important role in maintaining customer loyalty. Brand image is very important in influencing consumer decisions. Effective packaging and good product quality can help maintain the brand image of Yakult and this can maintain customer loyalty to continue choosing Yakult as a health drink. It is hoped that the results of this research can contribute to Public Relations courses and have practical implications in better understanding the role of branding image in maintaining customer loyalty.